MEMAHAMI SEBARAN KINERJA PENDIDIKAN INDONESIA: STUDI NERACA PENDIDIKAN DAERAH - Marihot Nasution (Pusat Kajian Anggaran, 2020)
This study examines the differences in the results of education development in Indonesia by differentiating these results by region. This is done to determine the weaknesses and weaknesses of each region so that subsequent development is directed to cover up existing weaknesses. The comparison of the regions is carried out by using the different test of the western and eastern regions on the performance of education development recorded in Neraca Pendidikan Daerah 2018/2019 published by the Ministry of Education and Culture. The results of the study note that educational performance in the western and eastern regions of Indonesia has a statistically significant difference. Especially in performance as measured by pure participation rates and national examination results at all levels of education tested. The eastern region has a weaker educational performance than the western region of Indonesia. This needs to be a concern for the government if it wants to reduce development inequality in the education sector.